PERSPEKTIF IMAM AL-QURTHUBI DALAM PENAFSIRAN SURAT AL-MAIDAH AYAT 89 TENTANG KIFARAT YAMIN - Masykar, Tabsyir (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2021)
Yamin or Oath is swearing a speech to convince others of his words by mentioning the name of Allah swt. There are so many among the Islamic community that they take the oath easily, but they do not care about the effect on the oath they have taken. So that some of them break the oath a lot without knowing what kifarat to do when they break the oath. The author intends to examine the interpretation of the kifarat oath and the procedures for carrying out the kifarat oath in surah al-maidah verse 89 which is mentioned in the book Al-jami 'Fi Ahkam Al-Qur'an by Imam Al Qurtubi. This study uses a descriptive methodology of analysis of the results of the literature review. The results of this study found that Imam Al-Qurtubi in his interpretation mentioned an oath that caused a kifarat and an oath that did not cause a kifarat. There are at least four types of oath models with various models of procedures for carrying out the oath.